Relationship between the features of Information System (IS) and job satisfaction among staff at Petronas Dagangan Berhad ( PDB ) Johor Bahru / Nur Fairus Farhana Abdul Rahman - Abdul Rahman, Nur Fairus Farhana (Faculty of Business and Management, 2013)
This study was conducted to explain the relationship between the features of Information Quality (IS) quality and job satisfaction among staff at Petronas Dagangan Berhad (PDB) lohor Bahru. The study was carried out at Petronas Dagangan Berhad (PDB) Johor Bahru which are includes of PDB in southern region such as PDB Bandar Baru Uda, PDB Senai Aviation Fuel Terminal, PDB Pasir Gudang LPG Fuel Terminal and PDB Pasir Gudang LPG Bottling Terminal. The study involved 100 respondents with the staffs are from different categories of position levels which includes of top< middle and bottom levels of staffs from different departments. The researcher studies this topic because to identify on how the features of information system quality can relating with the job satisfaction towards the staffs. Additionally, the research objective for this study is indicates to identify the level of job satisfaction among the staff at Petronas Dagangan Berhad (PDB) lohor Bahru, to investigate the relationship between system quality on job satisfaction staff at Petronas Dagangan Berhad (PDB) Johor Bahru, to determine the relationship between information quality on job satisfaction among staff at Petronas Dagangan Berhad (PDB) Johor Bahru and to examine the relationship between service quality on job satisfaction among staff at Petronas Dagangan Berhad (PDB) Johor Bahru. Furthermore, each staffs from the different levels of employment and department may present a different perceptive ofthe surveys.